Efeito de óleos essenciais na inibição in vitro de Geotrichum citri-aurantii - Chignolli, Maria Clara (Universidade Federal de São Carlos, 2026)
Citrus production represents an important sector of Brazilian agribusiness, with particular emphasis on orange cultivation. However, it is highly susceptible to pathogens that compromise postharvest quality, such as the fungus Geotrichum citri-aurantii, the causal agent of sour rot in citrus fruits, resulting in significant losses in fruit quality and marketability. In Brazil, there are currently no registered products for the control of this pathogen. Given this scenario, natural products have been investigated as an alternative for disease management. Therefore, the objective of this study was to evaluate the in vitro activity of the essential oils of Pêra orange, clove, cinnamon, and lemongrass against G. citri-aurantii. In vitro assays were conducted to evaluate the antifungal effect of essential oils extracted from dried flower buds (clove), mature fruit peels (Pêra orange), dried trunk bark (cinnamon), and fresh leaves (lemongrass). Concentrations of 0.25, 0.50, 1, 2, 4, 8, and 16 μL mL⁻¹, along with a negative control (without essential oil), were incorporated into Potato Dextrose Agar medium to evaluate changes in hyphal morphology, inhibition of mycelial growth, sporulation, and conidial germination of G. citri-aurantii. The experiment was conducted in a completely randomized design using a 4 × 7+1 factorial arrangement. The essential oils of clove, cinnamon, and lemongrass exhibited satisfactory antifungal activity against the pathogen. Cinnamon essential oil stood out by providing high inhibition of mycelial growth (92.74%) even at the lowest concentrations tested (0.25 μL mL⁻¹), followed by clove essential oil (61.77%), whereas lemongrass essential oil was effective from 1 μL mL⁻¹ onward (70.52%). In contrast, Pêra orange essential oil showed no antifungal activity against the pathogen, promoting its development at concentrations of 8 and 16 μL mL⁻¹ (−21.22% and −36.18%, respectively). Furthermore, regarding hyphal morphology, treatments with cinnamon, lemongrass, and Pêra orange essential oils induced alterations such as vacuolization, cytoplasmic disorganization, leakage of cellular contents, and hyphal rupture, reinforcing their antifungal potential.
Effect of essential oils on the in vitro inhibition of Geotrichum citri-aurantii
Keywords: Citricultura; Controle alternativo; Citrus × sinensis; Cymbopogon citratus; Syzygium aromaticum; Cinnamomum verum; Citrus production; Alternative control; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; 2. Fome Zero e Agricultura Sustentável; 12. Consumo e Produção Responsáveis